Financial Implication of COVID-19: A Story of Malaysian Dental Practitioner - Nor Faharina Abdul Hamid; Nurul Haini Najwa Mohamd Mahmod; Raja Nur Nabiha Raja Amir Hamzah; Azlan Jaafar (Faculty of Dentistry Universitas Indonesia, 2024)
Indexed by WOS